Patient Safety Incident Reporting Challenges in Indonesian Private Hospitals - Listiowati, Ekorini; Arini, Merita; Nurmansyah, Mochamad Iqbal; Rachmawati, Emma; Samsudin, Agus (Global Medical & Health Communication (GMHC), 2024)
Reporting patient safety incidents is essential in improving learning and patient safety. It is necessary to identify reporting challenges to improve the reporting process's success. This study assessed the challenges of patient incident reporting and learning systems in Indonesian private hospitals. This qualitative participatory action research is used. In October 2022, data was collected using a videoconferencing application. This study included 34 quality improvement and patient safety team members from 22 private hospitals. In this study, inductive analysis was used. The challenges of patient safety incident reporting are examined in six categories in this study: reporting environment, reporting rules and content, analysis and investigation, governance, action and learning, and patient and family engagement. The challenges mostly come from reporting environment components such as reporting difficulty and ignorance, a lack of time for analysis, the fear of making a mistake in the reporting process, and insufficient management support. Multiple challenges were encountered in different patient safety incident components. A positive environment for reporting patient safety incidents needs a multifaceted approach, including increased hospital leadership commitment and policies and procedures.